2013
DOI: 10.3402/gha.v6i0.21618
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and attitudes towards epilepsy in Tehran, Iran

Abstract: BackgroundEpilepsy is a prototypical, stigmatised disorder. Numerous studies have been conducted regarding the public perception of epilepsy, but they are primarily from high-income western countries; few studies have taken place in low- to middle-income countries with a traditional culture and a religious orientation.ObjectiveThe public knowledge and attitudes towards epilepsy in Tehran, Iran, is studied.DesignA survey of 800 subjects ranging from 18 to 85 years was randomly chosen from households in Tehran i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 19 publications
2
27
1
3
Order By: Relevance
“…A higher level of education and larger family size correlated with a higher percentage of correct responses to the knowledge questions. This result is consistent with findings of other study [32]. A relationship was found between increased level of education and the female gender with attitudes about epilepsy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A higher level of education and larger family size correlated with a higher percentage of correct responses to the knowledge questions. This result is consistent with findings of other study [32]. A relationship was found between increased level of education and the female gender with attitudes about epilepsy.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, other studies in between different ethnic groups and school's teachers in Iran indicated that the level of awareness about epilepsy was quite high and teachers had positive attitude about epilepsy [4, 31]. Public awareness of epilepsy in Iran showed similar to studies conducted in high income western countries [32]. There was a significant association between an increase in knowledge score and an increase in family size and educational level in the present study that correlates with the findings of other studies [29, 34].…”
Section: Discussionmentioning
confidence: 68%
“…The proportion of survey respondents objecting to a person with epilepsy marrying a close relative, are similar to those from some other sub Saharan African countries [26, 27] but lower compared to an earlier study from Cameroon [16]. Interestingly, there were no differences in response to this question related to survey respondent demographics among the study participants.…”
Section: Discussionsupporting
confidence: 71%
“…Cultural, familial and individual variations in understanding of epilepsy, 59–62 heritability 63 and risk 64 also need to be addressed. People in families affected by epilepsy may have ‘personal theories of inheritance’ based on their perceptions of shared physical or personality traits among family members.…”
Section: Provision Of Genetic Servicesmentioning
confidence: 99%